2015
DOI: 10.3141/2476-11
|View full text |Cite
|
Sign up to set email alerts
|

Distracted Motor Vehicle Driving at Highway–Rail Grade Crossings

Abstract: Distracted driving of a motor vehicle increases a driver's susceptibility to crash involvement. Such driving in the vicinity of highway–rail grade crossings (HRGCs) is especially perilous because the distracted driver may not be aware of the presence of an approaching train. Train-involved motor vehicle crashes invariably cause more severe injuries and greater property damage than other motor vehicle crashes. Because distracted driving at HRGCs is somewhat underresearched, the objectives of this research were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…While drivers tend to look toward the advanced signage on the approach of level crossings, no research has assessed whether the poor driver behavior observed at level crossings is a consequence of a problem of maladaptive behavior (25) with drivers not understanding what they need to do at crossings, or a looked-but-failed-to-see error as suggested by Rudin-Brown et al (10). Tung and Khattak have also shown that distraction is prevalent at railway level crossings in the U.S., reaching 30% on average, and resulting in similar risky approaches at crossings (18). With increasing road and rail traffic volumes, of the order of 35% in recent years in New Zealand for instance (26), the trend of increasing collisions at level crossings is likely.…”
mentioning
confidence: 99%
“…While drivers tend to look toward the advanced signage on the approach of level crossings, no research has assessed whether the poor driver behavior observed at level crossings is a consequence of a problem of maladaptive behavior (25) with drivers not understanding what they need to do at crossings, or a looked-but-failed-to-see error as suggested by Rudin-Brown et al (10). Tung and Khattak have also shown that distraction is prevalent at railway level crossings in the U.S., reaching 30% on average, and resulting in similar risky approaches at crossings (18). With increasing road and rail traffic volumes, of the order of 35% in recent years in New Zealand for instance (26), the trend of increasing collisions at level crossings is likely.…”
mentioning
confidence: 99%
“…With regard to highway-railway grade crossing safety issues, several studies discuss various aspects of crossing safety (Saccomanno et al, 2004;Millegan et al, 2009;Chaudhary et al, 2011;Chadwick et al 2014;Tung et al, 2015;Wang et al, 2016a;Heydari et al, 2016b;Haleem, 2016;Liu and Khattak, 2017;Hsu and Jones, 2017;Sperry et al, 2017;Zhang et al, 2017;Larue et al, 2018;Beanland et al, 2018). Many grade crossing studies can be divided into two categories: (1) crash-frequency studies (Hauer and Persaud, 1987;Austin and Carson, 2002;Saccomanno and Lai, 2005;Park and Saccomanno, 2005;Oh et al, 2006;Yan et al, 2010;Medina and Benekohal, 2015;Heydari and Fu, 2015;Lu and Tolliver, 2016;Heydari et al, 2016a;Heydari et al, 2017b; Guadamuz-Flores and Aguero-Valverde, 2017); and (2) crash-consequence studies (Eluru et al, 2012;Hao et al, 2015;Ghomi et al, 2016;Zhao et al, 2018).…”
Section: Unobserved Heterogeneitymentioning
confidence: 99%
“…Most of the previous research studies have focused on roadway intersection or roadway crashes [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Relatively little research effort has focused on HRGC accidents compared to roadway accidents [15][16][17][18][19][20][21][22][23][24]. Moreover, among all the previous HRGC accident analyses, the majority of them focus only either on crash frequency, often based on crossing inventory databases [19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], or on crash severity analysis, often based on historical crash police report databases [16,[40][41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%